The strategies used by the school health team during the delivery of sexual health information to unmarried adolescents in Malaysia (Belitung Raya Foundation, Indonesia, 2022)
Background: Adolescents’ sexual health is vital to overall health and well-being to achieve sustainable development goals. Yet, research on the strategies used by Malaysian school health teams regarding their experiences of providing sexual health information to adolescents is sparse. Objective: This study was conducted to explore the experiences of school health teams in Malaysia who provide unmarried adolescents with sexual health information either during school health visits or at health clinics, with a particular interest in the strategies they use to educate these young people. Methods: This qualitative study used semi-structured interview data from twenty participants from four multidisciplinary school health teams. The participants included staff nurses, medical officers, and family medicine specialists. The transcripts were analysed for common themes. Results: Four main themes were identified: discourse on risk, being selective, using scare tactics and maintaining own honour. The findings indicate that the interactions between school health teams and unmarried adolescents were not always ‘adolescent friendly’. The school health teams tended to use discourses of ‘risk’ or scare tactics to encourage abstinence in the adolescents they advised. Staff were also selective about the information they gave, prioritising notions of ‘maintaining honour’ over ‘safer sex’ messages. Conclusion: This study revealed how school health teams perceived sexual health education to be about moral issues and social attitudes. Influenced by both culture and religion, the sexual health services provided were underpinned by a ‘moral’ approach and promoted abstinence. However, most of the nurses in this study held the belief that sexual health knowledge acts as an encouragement for sexual activity. Thus, as part of school health teams, nurses need to embrace evidence that improved sexual health education may delay sexual initiation and prevent unintended pregnancy and HIV/STDs.